2021
DOI: 10.1002/rcr2.802
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel‐induced interstitial lung disease among patients with breast cancer: a case series and review of literature

Abstract: Taxane‐induced pneumotoxicity is rare. However, 1–5% of patients taking docetaxel may develop severe pneumotoxicity. This has been limited to case reports in the literature. We report seven breast cancer patients who developed docetaxel‐induced diffuse parenchymal lung disease (DPLD) of an organizing pneumonia pattern on high‐resolution computed tomography (HRCT). The patients presented with progressive breathlessness within four weeks of the final dose. All had an organizing pneumonia pattern on their HRCTs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The most common form is interstitial pneumonitis which can develop within days to weeks following receiving docetaxel and paclitaxel or it can arise in the later course of the therapy (4). The largest case series described 18 cases of interstitial pneumonitis which developed following docetaxel show bilateral reticular or nodular patterns or ground glass opacities predominantly in the periphery of upper lungs (6). Doxorubicin can very rarely cause OP, but direct co-relation is not proven (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common form is interstitial pneumonitis which can develop within days to weeks following receiving docetaxel and paclitaxel or it can arise in the later course of the therapy (4). The largest case series described 18 cases of interstitial pneumonitis which developed following docetaxel show bilateral reticular or nodular patterns or ground glass opacities predominantly in the periphery of upper lungs (6). Doxorubicin can very rarely cause OP, but direct co-relation is not proven (1).…”
Section: Discussionmentioning
confidence: 99%
“…OP pattern in docetaxel-induced pneumotoxicity is yet to be defined in terms of the time of onset and major contributing risk factors. Based on current literature, patients with underlying chronic lung disease, lung malignancy and those who have had radiotherapy are known to be at high risk of developing lung injury (6). Paclitaxel is more pneumotoxic than docetaxel.…”
Section: Hrct Images On Diagnosismentioning
confidence: 99%
“…In a study conducted by Hettiarachchi et al reported that patients with prior lung anomaly were shown to have increased risk of ILD. 4 The incubation period between the administration of the drug and the onset of lung injury is mostly unpredictable but most studies have a mean time gap of about 15±3 days. In a study by Manuprasad et al conducted on 477 patients, the median time gap from administration of last dose to onset of symptoms and median hospital stay were 16 days (8-28 days) and 8.5 days (7-18 days) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone combination therapy analysed in this study included either a GnRH agonist or GnRH antagonist in combination with an ARA or an ASI, or a GnRH agonist or GnRH antagonist in combination with an ARA and an ASI. We then chose taxanes, including paclitaxel, docetaxel and cabazitaxel, as a positive control because they are associated with ILD and widely used for the treatment of prostate cancer 10,20,21 …”
Section: Methodsmentioning
confidence: 99%
“…We then chose taxanes, including paclitaxel, docetaxel and cabazitaxel, as a positive control because they are associated with ILD and widely used for the treatment of prostate cancer. 10,20,21 After indication, adverse event and primary suspected drug identified, we divided included cases into 3 groups: (i) the hormone therapy group, which were treated with hormone therapy agents as primary suspected drugs; (ii) the taxane group, a positive control group which were treated with taxanes as primary suspected drugs; and (iii) the other primary suspected drug group, a negative control group, which were treated with other primary suspected drugs. We further excluded cases aged <18 years, cases with ILD complications before medication, cases in the hormone therapy with taxanes combination, cases in the taxane group with hormone therapy combination, or hormone combination therapy cases without the defined combination above.…”
Section: With Prostate Cancer Indication In the Indi Table According Tomentioning
confidence: 99%